3D-Printed Fluorescence Hyperspectral Lidar for Monitoring Tagged Insects - Manefjord, Hampus (2023)
Insects play crucial roles in ecosystems, and how they disperse within their habitat has significant implications for our daily life. Examples include foraging ranges for pollinators, as well as the spread of disease vectors and pests. Despite technological advances with radio tags, isotopes, and genetic sequencing, insect dispersal and migration range remain challenging to study. The gold standard method of mark-recapture is tedious and inefficient. This paper demonstrates the construction of a compact, inexpensive hyperspectral fluorescence lidar. The system is based on off-the-shelf components and 3D printing. After evaluating the performance of the instrument in the laboratory, we demonstrate its efficient range-resolved fluorescence spectra in situ. We present daytime remote ranging and fluorescent identification of auto-powder-tagged honey bees. We also showcase range-, temporally- and spectrally-resolved free-flying mosquitoes, which were tagged through feeding on fluorescent-dyed sugar water. We conclude that violet light can efficiently excite administered sugar meals imbibed by flying insects. Our field experiences provide realistic expectations of signal-to-noise levels, which can be used in future studies. The technique is generally applicable and can efficiently monitor several tagged insect groups in parallel for comparative ecological analysis. This technique opens up a range of ecological experiments, which were previously unfeasible.